2003
DOI: 10.1161/01.cir.0000066695.24697.07
|View full text |Cite
|
Sign up to set email alerts
|

Stenting of Culprit Lesions in Unstable Angina Leads to a Marked Reduction in Plaque Burden: A Major Role of Plaque Embolization?

Abstract: Background-Intravascular ultrasound (IVUS) studies have shown that a mechanism of plaque compression/embolization contributes toward the poststenting increase in lumen area. The aim of this IVUS study was to compare the mechanisms of lumen enlargement after coronary stenting in 54 consecutive patients with unstable angina (UA) (group 1) and 56 with stable angina (group 2) to verify whether plaque embolization plays a major role in the former. Methods and Results-Both groups underwent the IVUS assessment (speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 38 publications
1
37
1
3
Order By: Relevance
“…[18][19][20][21][22] In addition to the effect of plaque burden, specific plaque characteristics, such as lipid pool-like image, intracoronary mural thrombus, or ultrasonic attenuation (assessed by grayscale IVUS), have been shown to be related to the no-reflow phenomenon during PCI in patients with ACS. 23- 27 Recently, radiofrequency signal-derived IVUS tissue characterization has been developed to provide objective and quantitative information for predicting distal microembolization and slow flow during PCI.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] In addition to the effect of plaque burden, specific plaque characteristics, such as lipid pool-like image, intracoronary mural thrombus, or ultrasonic attenuation (assessed by grayscale IVUS), have been shown to be related to the no-reflow phenomenon during PCI in patients with ACS. 23- 27 Recently, radiofrequency signal-derived IVUS tissue characterization has been developed to provide objective and quantitative information for predicting distal microembolization and slow flow during PCI.…”
Section: Discussionmentioning
confidence: 99%
“…In general, angiographic appearance of flow, dissection, and mechanical side-branch occlusion were all poorly predictive of new MRI-defined injury, which possibly implies the important role of collateral vessels and of plaque lesion composition in the occurrence of irreversible injury. 22 …”
Section: Discussionmentioning
confidence: 99%
“…The net loss of plaque volume was thought to represent a combination of plaque redistribution, compression, and/or embolization. In patients with severe unstable angina (with no glycoprotein IIb/IIIa inhibition or clopidogrel), Prati et al 18 were able to show a PCI-related pronounced reduction in plaque volume, and reduction in plaque area was directly proportional to the rise in CK-MB. In patients undergoing primary PCI, Sato et al 19 demonstrated a decrease in plaque volume that was significantly larger in patients with inadequate reflow than in those with normal reflow and showed that changes in plaque volume were significantly correlated with c-TFC after PCI.…”
Section: Discussionmentioning
confidence: 99%